1940
DOI: 10.1017/s0022029900017672
|View full text |Cite
|
Sign up to set email alerts
|

259. A note on a simple and accurate viscosimetric form of rennet test

Abstract: Since publication (1) the apparatus previously described by the authors has been altered and improved. The alterations have been concerned mainly with excluding draughts and securing a better form of support. In using the apparatus we have found that the absence of vibration is important for the agreement of duplicates. It would seem that vibration tends to break the cohesion between the curd and the surface of cylinder A. For this reason a part of the laboratory as free as possible from vibrational disturbanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1942
1942
1987
1987

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Following 5 min. of stirring, the solution was brought to pH [6][7][8] with N/1 NaOH and then heated quickly to 80° C. to inactivate native proteases of the milk (13). This process generally removed the alcohol and acetone and brought into solution any undissolved particles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following 5 min. of stirring, the solution was brought to pH [6][7][8] with N/1 NaOH and then heated quickly to 80° C. to inactivate native proteases of the milk (13). This process generally removed the alcohol and acetone and brought into solution any undissolved particles.…”
Section: Methodsmentioning
confidence: 99%
“…Viscometric analyses have been used to measure the rate of clotting of milk (3,4,5,6,7) and to gain specific information about the phases of the renneting processes. On the basis of viscometric study of solutions of casein in NaOH, Jirgensons (8) suggested that casein particles decreased in symmetry (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, an automatic coagulation time recorder was developed modelled on the principle used by Randall (2) in an apparatus for testing heparin. This instrument promised considerable advantages in convenience and accuracy over previously described forms of apparatus (3,4,5,6,7,8,9).…”
Section: Introductionmentioning
confidence: 99%